MANAJEMEN CAIRAN PADA PASIEN PENYAKIT GINJAL KRONIS YANG MENJALANI HEMODIALISIS - Wahyu Lestari; Ahmad Asyrofi; Hendra Adi Prasetya (Universitas Widya Husada Semarang, 2018)
Introduction: The cause of serious problems in patients with chronic kidney disease on hemodialysis is due to uncontrolled fluid intake problems. Factors affect the restriction of patient's fluid intake include internal factors such as age, education, level duration of hemodialysis therapy and external factors such as closest people relationships. Method: Analytical descriptive method with total sampling; 57 patients at Dr. H. Soewondo Kendal Hospital. The instrument used Fluid Management Instrument from António Filipe (2015). Result: fluid restriction mostly in bad category were 55 respondents (96,5%) and salt reduction in bad category 47 respondent (82,5%). Discussion: It is advisable to the hospital to require education and evaluation for the patient about structured fluid management by health personnel so that people with chronic kidney disease (CKD) on hemodialysis in accordance with the expected results more leverage.